Advances in the understanding of haemoglobin switching - Sankaran, Vijay G. (2010)
The study of haemoglobin switching has represented a focus in haematology due in large part to the clinical relevance of the fetal to adult haemoglobin switch for developing targeted approaches to ameliorate the severity of the β-haemoglobinopathies. Additionally, the process by which this switch occurs represents an important paradigm for developmental gene regulation. In this review, we provide an overview of both the embryonic primitive to definitive switch in haemoglobin expression, as well as the fetal to adult switch that is unique to humans and old world monkeys. We discuss the nature of these switches and models of their regulation. The factors that have been suggested to regulate this process are then discussed. With the increased understanding and discovery of molecular regulators of haemoglobin switching, such as BCL11A, new avenues of research may lead ultimately to novel therapeutic, mechanism-based approaches to fetal haemoglobin reactivation in patients.